THE EXAMINATION OF THE IMPACT OF CUSTOMER VALUE ON CONSUMER BEHAVIOR AMONG MINIMARKET RETAIL PATRONS IN THE JABODETABEK - Tiffany, Abigael; Wijaya, Niko Putra; Djahran, Mohammad Ansara; Wijaya, Lianna (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
Minimarkets represent a critical sector within the retail industry, playing a fundamental role in fulfilling the daily requirements of consumers, amidst a persistent uptrend in sales value. Within the progressively competitive commercial environment, the comprehension of Customer Value has emerged as a pivotal element in augmenting Satisfaction, consequently fostering customer Loyalty, which stands as a crucial component of Consumer Behavior and is essential for ensuring the continuity of business operations. The principal aim of this research is to examine the influence of Customer Value on Consumer Behavior among minimarket customers in the Jabodetabek area. A total of 376 minimarket customers in Jabodetabek area were surveyed via an online questionnaire for data collection. The methodological approach utilized for data analysis involved the application of Structural Equation Modeling using SmartPLS 4.0. The results of hypothesis testing indicate that Customer Value factors such as Product Excellence, Service Excellence, Social Value, and Aesthetics play a crucial role in influencing customer Satisfaction. Nevertheless, the Efficiency dimension does not demonstrate a notable impact on Satisfaction. Furthermore, customer satisfaction plays a significant role in fostering customer loyalty. The conclusions drawn from this study emphasize the need for minimarket businesses to continuously assess customer satisfaction levels by leveraging Customer Value, in turn enhancing customer loyalty and nurturing more resilient links between minimarkets and consumers in the Jabodetabek region.